Analysis Study of Outcomes Robotic-Assisted Surgery is Compared to Minimally Invasive Surgery in Pediatric Urology: A Comprehensive Systematic Review and Metaanalysis Study - Tegar Pamungkas; John M.Sangkai (International Medical Journal Corp. Ltd, 2024)
Background: The use of robotic-assisted surgery (RAS) has increased more slowly in pediatrics than in the adult population. Despite the many advantages of robotic instruments, such as the ability to mimic the movements of the human wrist, highly magnified 3D visualization, and tremor filtration, the da Vinci Surgical System still presents some limitations for use in pediatric surgery. Method: This systematic review and meta-analysis, conducted following PRISMA guidelines and employing the PICO format, aim to explore about the analysis study of outcomes robotic-assisted surgery is compared to minimally invasive surgery in pediatric urology. Inclusion criteria encompass diverse study designs (RCTs, observational, quasi-experimental, and case-control studies) investigating the analysis study of outcomes robotic-assisted surgery is compared to minimally invasive surgery in pediatric urology, while exclusion criteria filter out studies lacking relevance to the analysis study of outcomes robotic-assisted surgery is compared to minimally invasive surgery in pediatric urology. Result: The selected articles, demonstrate a recent publication trend, with 2 are articles published in PubMed journal, 5 were published in Sage Journal, 1 were published in Lancet, 4 were published in Science Direct from 2014 – 2024. Based on the Z value of 12.79 and P value <0.00001, there is a significant comparison between robotic-assisted surgery and minimally invasive surgery. The fixed random value is 0.37, where the value here is positive. Conclusion: Robotic procedures in paediatric surgery are increasingly reported. Financial restrictions in many public health markets will likely demonstrate a reduced growth. Over the next decade, the introduction of new, more affordable robotic platforms is likely to alter this.